Supercritical fluid extraction of bioactive flavonoid from Strobilanthes crispus (pecah kaca) and its comparison with solvent extraction - Md Salleh, Liza; Abdul Rahman, Russly; Bimakr, Mandana; Selamat, Jinap; Rahmat, Asmah; Sarker, Md. Zaidul Islam; Abdul Hamid, Azizah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Supercritical carbon dioxide extraction (SC-CO 2) of bioactive flavonoid from Strobilanthes crispus (Pecah Kaca) was performed to study the effects of various parameters such as pressure, temperature and dynamic extraction time on the yield and composition of bioactive flavonoid. The results were also compared with those obtained by conventional Soxhlet extraction in lab conditions. The results from SFE showed that the effect of extraction variables on extraction yields decreased in the following order: pressure, temperature and dynamic extraction time. The extraction pressure played a dominant role in the yield of the sample while the effect of time could be ignored. This study also revealed that both Soxhlet extraction and SC-CO 2 extraction can be used to obtain flavonoid compound. Under the optimum conditions, the highest bioactive flavonoid compound content was obtained at 3.98% and eight flavonoid compounds were identified by HPLC.